Impact of COVID-19 on Medical Supply in Adults With Congenital Heart Disease - Akkermann, Steffen; Halling, Tim; Löffler, Friederike; Silber-Peest, Ann S.; Krüger, Tillmann; Bleich, Stefan; Bauersachs, Johann; Kahl, Kai G.; Westhoff-Bleck, Mechthild (Frontiers in Psychiatry, 2022)
Introduction: In March 2020, the World Health organization declared COVID-19 a global pandemic. One year later, the direct and indirect burden of the COVID-19 pandemic become more visible. In this context, there is concern about the allocation of medical resources and medical treatment of other diseases than COVID-19. Particularly, patients with chronic diseases need constant medical and pharmacological treatment. Therefore, we evaluated a large cohort of patients with adult congenital heart disease (ACHD) regarding postponed medical appointments and their possibilities to receive medical treatment during the COVID-19 pandemic. Methods: This cross-sectional study included 559 patients with ACHD (mean age 37.32 +/-11.98; 47% female). Clinical characteristics, answers to questionnaires concerning lifestyle, psychological well-being, addictive behavior and adherence were related to postponed medical appointments and limited access to medical care. Results: One hundred and nine patients (19.5%) reported problems getting necessary medical treatment or visiting a physician. Higher anxiety levels (p=0.004) emerged as the main factor associated with medical undertreatment. The main risk factors for postponement of least one medical appointment (n=91) were higher depression (p=0.013) and anxiety (p=0.05) symptoms as well as female sex (p=<0.0001) and documented arrhythmias (p=0.007) indicating a particular risk group of cardiovascular complications. In contrast, frequent physical activity identified patients at lower risk. Conclusion: In ACHD anxiety and depressive symptoms handicap patients to receive medical care. Postponement of medical appointments additionally relates to female sex and documented arrhythmias. The latter indicates that patients at high risk of adverse cardiac outcome avoid routine medical care Our data may lead policy makers to develop strategies for the provision of medical services to particular vulnerable patient groups, and to optimize management of both future pandemics and daily routine.